Estudo das relações entre descargas sólidas e líquidas obtidas por meio de diferentes métodos de medição - Grutka, Letícia (2013)
The objective of this work was to study the relationship between liquid discharge and suspended sediment discharge by various methods. The study was carried out at Menino Deus IV Fluviometric Station, located in Santa Maria/RS. It was relating to solid discharge in suspension, using all samples in full waves and without precipitation, with the liquid discharge using the integrated sampler USDH 48 and ISCO sampler punctual. The coefficient of determination of 93.4 % and 85.0 %, were obtained respectively, to the samplers USDH 48 and ISCO, can be considered a good correlation. Also were related the turbidity with the sediments concentration in suspension, obtaining the solid discharge calculated with the liquid discharge using the sampler integrator USDH 48. A correlation coefficient of 93.0 % with all samples and the ISCO 85.2 % were obtained. It was observed that the automatic measurements by turbidity become a viable alternative due to the easy to install and to possible a continuous monitoring and automatic, without the presence of a technician in place, further obtaining similar results to the traditional methods which is recommended in this study. To determine the liquid discharge, the hydrometric windlass traditional method and the acoustic method was used, using an Acoustic Doppler Profiler (ADP). It can be concluded that with the depths less than 0.28 m, the ADP did not execute the reading speed and the presented reading failures. Thus, for measurements in these conditions, it is suggested to use the hydrometric windlass, because it is a device that provides more detail and flexibility when handling.